Characterization of a Protein Phosphatase Type-1 and a Kinase Anchoring Protein in Plasmodium falciparum - Lenne, Astrid; De Witte, Caroline; Tellier, Géraldine; Hollin, Thomas; Aliouat, El Moukhtar; Martoriati, Alain; Cailliau, Katia; Saliou, Jean-Michel; Khalife, Jamal; Pierrot, Christine (Frontiers in Microbiology, 2018)
With its multiple regulatory partners, the conserved Protein Phosphatase type-1 (PP1) plays a central role in many functions of the biology of eukaryotic cells, including Plasmodium falciparum. Here, we characterized a protein named PfRCC-PIP, as a major partner of PfPP1. We established its direct interaction in vitro and its presence in complex with PfPP1 in the parasite. The use of Xenopus oocyte model revealed that RCC-PIP can interact with the endogenous PP1 and act in synergy with suboptimal doses of progesterone to trigger oocyte maturation, suggesting a regulatory effect on PP1. Reverse genetic studies suggested an essential role for RCC-PIP since no viable knock-out parasites could be obtained. Further, we demonstrated the capacity of protein region containing RCC1 motifs to interact with the parasite kinase CDPK7. These data suggest that this protein is both a kinase and a phosphatase anchoring protein that could provide a platform to regulate phosphorylation/dephosphorylation processes.